ANALISIS BIAYA DAN PENDAPATAN USAHA TANI WORTEL DI KABUPATEN KARANGANYAR - MEI TRI SUNDARI (Universitas Sebelas Maret, 2011)
The objective of this research is to know the revenue, cost and income in carrot farm. It wants to know the efficiency of carrot farm in Karanganyar Regency. The method used in this research was analytical descriptive with survey in implementation. The location was selected purposively and it was selected by 5 district which producing carrot that is Jatiyoso, Tawangmangu, Ngargoyoso,Karangpandan and Jenawi. From those district selected village by random. Selection of sample from each village use method “Simple Random Sampling